The implementation of a static air-foam hybrid mattress in a nursing home population: a feasibility study. (2nd November 2022) - Raepsaet, Charlotte; Beeckman, Dimitri
Abstract : Background/Aims: Nursing home residents are at higher risk of developing pressure ulcers as a result of comorbidities, changes in skin texture and function, incontinence, and limited mobility, such as residents who are mostly bedbound. The aim of this study was to evaluate the introduction and use of a static air-foam hybrid mattress based on the experiences of nurses and to assess the incidence of pressure ulcers in a nursing home population at risk for developing pressure ulcers over a 14-day period. Methods: A multicentre clinical trial, followed by focus group interviews with nurses, was conducted between August and October 2020 to evaluate the implementation and use of a static air-foam hybrid mattress. Residents ( n =29) at risk of developing pressure ulcers were placed on the mattress for 14 days. Skin and risk assessments were performed daily. At the end of the study, nurses ( n =9) were invited to participate in focus group interviews to share their experiences. Results: During the study period, none of the residents developed stage 2–4 pressure ulcers. Based on nurses' experiences with the mattress, five themes were identified: design and guidance, pump use, mobility and positioning, mattress appearance and clinical opinion. Results indicated that the mattress provided a clinically effective support surface in the prevention of pressure ulcers and was easy to use. Conclusions: A static air-foam hybrid mattress provides a clinically effective support surface in the prevention of pressure ulcers. Nurses preferred the mattress to an alternating pressure mattress and a static air mattress overlay.